Strengthening the Competitiveness of Higher Education Institutions Through a SWOT Analysis Approach at UNTARA - Slamet Riyanto; Sutarman (Journal of Economics and Management, 2026)
This study aims to analyze strategies for strengthening the competitiveness of higher education institutions through a SWOT analysis approach at UNTARA. Increasing competition among universities requires institutions to formulate effective strategies to enhance academic quality, institutional performance, and stakeholder trust. This research employs a qualitative descriptive method to identify internal factors, including strengths and weaknesses, as well as external factors, namely opportunities and threats, faced by UNTARA. Data were collected through document analysis, interviews, and observations involving university leaders, lecturers, and administrative staff. The results indicate that UNTARA possesses significant strengths in institutional commitment, human resource potential, and community engagement, while facing challenges related to infrastructure development, research productivity, and digital governance. Externally, opportunities arise from policy support, growing demand for higher education, and technological advancement, whereas threats include intense competition, rapid changes in educational standards, and globalization. Based on the SWOT matrix, several strategic alternatives are proposed, including optimizing human resource development, improving academic quality assurance, strengthening partnerships, and enhancing institutional governance. These strategies are expected to sustainably strengthen UNTARA's competitiveness.